Role of Big Data – Shaping the Future of Project Management - Savio, Rajesh Dominic; Tamim, Wesam N (Eximia, 2023)
Big data is reshaping the future of the project management by ushering in new era of data driven decision-making processes and improving efficiency in the organization. It is through the transformative force of big data that it has revolutionized the way in which projects are conceived and executed in different sectors. Project managers can rely on big data in integrating real-time data into the project management’s operations and gain historical insights on the trend and successes of the projects. In this article, the aim is to assess the role of big data in shaping the future of the project management initiatives. Key concepts are discussed including the role of big data in planning and delivery, and this involves identifying the possible bottlenecks affecting the success of the project. It outlines the significance of big data in the project team environment, with the big data encouraging collaboration among the project team improving their productivity level and efficiency in conducting their activities. It is also integral in knowledge management with project managers relying on big data analytics in understanding the market trends and analyzing historical data. Other issues discussed relevant to the future of project management is efficient risk management and quality management, which are critical aspects in improving success of the projects and reducing cost of operations. As such, the future of project management is big data analytics.